Congenital Heart Disease With and Without Cyanotic Potential and the Long‐term Risk of Diabetes Mellitus: A Population‐Based Follow‐up Study. Issue 7 (July 2016) - Madsen, Nicolas L.; Marino, Bradley S.; Woo, Jessica G.; Thomsen, Reimar W.; Videbœk, Jørgen; Laursen, Henning Bœkgaard; Olsen, Morten
Abstract : Background: Long‐term survival for persons born with congenital heart disease (CHD) is improved, but limited knowledge exists of this growing population's acquired cardiovascular risk profile. This study's purpose was to assess CHD survivors' risk for type 2 diabetes mellitus (T2DM) with attention to the impact of cyanotic CHD. Methods and Results: This population‐based cohort study included Danish subjects with CHD who were born between 1963 and 1980 and were alive at age 30 years. For each CHD case, we identified 10 individuals from the general population matched by sex and birth year, by using the Danish Civil Registration System. Complete follow‐up was obtained through Danish public registries for death, emigration, and T2DM (diagnosis and prescriptions record). We computed cumulative incidences and hazard ratios of developing T2DM after age 30 for 5149 CHD subjects compared with the general population. After adjusting for CHD severity, as well as age, sex, preterm birth, and extracardiac defects, we analyzed the impact of cyanotic compared with acyanotic CHD. By age 45 years, the cumulative incidence of T2DM after age 30 was 4% among subjects with CHD. Subjects with CHD were more likely to develop T2DM than the general population (hazard raio 1.4, 95% CI 1.1–1.6). Subjects CHD who had cyanotic defects were more likely to develop T2DM than were subjects with acyanotic CHD (hazard ratio 1.9, 95% CI 1.1–3.3). Conclusions: CHD survivors had an increased risk of developing T2DM after age 30. Patients with cyanotic CHD are at particular risk. Given the cardiovascular health burden of T2DM, attention to its development in CHD survivors seems warranted.